Ultra-high precision nano additive manufacturing of metal oxide semiconductors via multi-photon lithography - Chun Cao; Xianmeng Xia; Xiaoming Shen; Xiaobing Wang; Zhenyao Yang; Qiulan Liu; Chenliang Ding; Dazhao Zhu; Cuifang Kuang; Xu Liu (Nature Communications)
Abstract As a basic component of the versatile semiconductor devices, metal oxides play a critical role in modern electronic information industry. However, ultra-high precision nanopatterning of metal oxides often involves multi-step lithography and transfer process, which is time-consuming and costly. Here, we report a strategy, using metal-organic compounds as solid precursor photoresist for multi-photon lithography and post-sintering, to realize ultra-high precision additive manufacturing of metal oxides. As a result, we gain metal oxides including ZnO, CuO and ZrO2 with a critical dimension of 35 nm, which sets a benchmark for additive manufacturing of metal oxides. Besides, atomic doping can be easily accomplished by including the target element in precursor photoresist, and heterogeneous structures can also be created by multiple multi-photon lithography, allowing this strategy to accommodate the requirements of various semiconductor devices. For instance, we fabricate an ZnO photodetector by the proposed strategy.